1997
DOI: 10.7589/0090-3558-33.4.706
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Plague in a Gunnison's Prairie Dog Colony Complex From New Mexico

Abstract: A plague (Yersinia pestis) epizootic spread through Gunnison's prairie dogs (Cynomys gunnisoni), and possibly other rodent species, in the Moreno Valley in north-central New Mexico between winter 1984-1985 and autumn 1987. We observed the progress of the epizootic and subsequent population recovery at four prairie dog towns within the valley during this period. At two towns (Midlake and Val Verde) the prairie dogs were marked prior to the epizootic. At two additional towns (Vega and South Entrance) prairie dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 8 publications
1
49
0
Order By: Relevance
“…Barnes (1982) reported a recurrence of plague epizootics within 4 to 5 yr and Cully et al (1997) reported an epizootic again after 3 yr. Whether these cases in which the same colonies experience plague again represent a continued presence of infection among hosts in that area or a reintroduction of Y. pestis from surrounding areas is not known.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Barnes (1982) reported a recurrence of plague epizootics within 4 to 5 yr and Cully et al (1997) reported an epizootic again after 3 yr. Whether these cases in which the same colonies experience plague again represent a continued presence of infection among hosts in that area or a reintroduction of Y. pestis from surrounding areas is not known.…”
mentioning
confidence: 99%
“…Lechleitner et al (1968) found antibodies to Y. pestis in only one of 108 deer mice (Peromyscus maniculatus) (the one seropositive animal was sampled during the active epizootic) and Cully et al (1997) only found antibodies in prairie dogs. In both studies, the epizootic appeared to diminish over the course of about a year.…”
mentioning
confidence: 99%
See 3 more Smart Citations